Understanding Customer Loyalty in Fast-Food Restaurants: Exploring the Moderating Effect of Relational Benefits in the United Arab Emirates - Ali Ahmed Ali-Alsaadi; Luis Javier Cabeza-Ramírez; Luna Santos-Roldán; Miguel González-Mohíno (SAGE Open)
In recent years, the fast-food sector has experienced a significant surge in the United Arab Emirates (UAE), establishing itself as the most relevant channel in foodservice. While previous literature has studied factors such as service quality, customer satisfaction, and positive word-of-mouth (WOM) as determinants of customer loyalty, little attention has been paid to the moderating effects that relational benefits could have in this context. To address this gap, the present study aims to explore how relational benefits moderate the relationship between service quality and customer satisfaction to strengthen customer loyalty. We employed a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to analyze data collected from a sample of 303 customers in Fujairah (UAE). The results confirm that both service quality and relational benefits are significant predictors of customer loyalty through customer satisfaction and positive word-of-mouth. Additionally, we verified the moderation hypothesis, but with a negative sign, suggesting the need to balance strategies concerning relational benefits to harmonize customer perception.